Lady of the island - Atwood, Daryl (Daryl Atwood, 2014)
"Angela Montoya is a lady in all senses of the word. She works as a hostess in the Black Horse Bar in the Philippines. One marriage to a wealthy American turned disaster, she longs to find another American that will rescue her from a life of dismal poverty. When Angela met Pete, she was shocked by the unanticipated impact of true love. She can't help but follow in her mother's footsteps when she finds herself with child. Five years after Angela drove her true love Pete away and 8,000 mile from home, she finds herself on trial for murder."-- back cover